From Role Play to Real Play: Teaching Effective Role-Playing Facilitation Skills - Winnie Suen; Jennifer Hughes; Matthew Russell; Henri Lee; Anne Carr; Victoria A. Parker; Sandhya Rao (Association of American Medical Colleges, 2011)
Abstract Role-playing is an underutilized but useful educational tool for teaching skills. Its effectiveness is increased when the role-play is facilitated well. Teachers may not feel comfortable in the facilitator role and may need further training. In this learning session, clinicians and medical educators become more aware of different role-play facilitation strategies and how they could be used in different teaching environments. The workshop lasts from 90 minutes to 2 hours. Participants focus on their own facilitation skills to learn how to engage clinical trainees in role-plays. A PowerPoint presentation and Instructor's Guide are provided for use in running the workshop. The session has been provided at two conferences, one institutional and the other a regional conference. The session was well received both times. At the end of the sessions, 90% of participants felt more confident in their ability to use role-play as a teaching tool. Depending on the number of participants, there may be a need for more presenters. The optimal size seems to be between three and five learners in a group. If there are too many learners in a group, they do not have an opportunity to participate in skills practice. The session is currently planned so that four presenters are needed to run it. If the learner practice scenario uses two learners to play out a scenario with a third learner acting as facilitator, then need be only one presenter. To encourage the use of role-plays as a teaching tool, teachers must feel comfortable in their roles as facilitators. This session provides a brief training on some of the principles of effective facilitation, as well as ideas about various types of role-play formats and techniques.